Quality control studies of argyreia speciosa sweet leaves - Sahu, Alakh, N; Hemalatha, S; Sairam, K. (Moksha Publishing House, 2013)
The plant Argyreia speciosa Sweet (Syn: Argyreia nervosa Burm. f.), is a woody climber which belongs to the family Convulvulaceae. The plant is commonly known as Elephant creeper in English and in Hindi, it is known as 'Vryddhadaru". It has been used as a "Rasayana" drug (rejuvenating drugs) in the traditional Ayurvedic system of medicines. Authentication and identification has been done taxonomically. The quality control studies of the leaves have been performed as per WHO guidelines-1998. The leaf has been heart-shaped up to 1foot across, back with silvery hairs on the lower surface, glabrous above, white tomentose beneath and long stalked. The most distinct anatomical character in TS of petiole has been the occurrence of intra-xylary phloem, where the xylem is above and the phloem is below. Unicellular trichomes are numerous and are present in the dorsal side only. These palisade cells are rectangular in nature where the length is twice its breadth. Total ash (15.5% w/w), acid insoluble ash (3.6% w/w), water soluble ash (2.18% w/w), alcohol soluble extractive (1.66% w/w), water soluble extractive (3.56% w/w) and moisture content (14.07%) of the crude drug have been obtained. A fingerprint of fluorescence has been observed in fluorescence analysis. Chlorinated pesticide in first and second elute from column have been 0.034 and 0.081mg/kg of the crude drug respectively. Phosphated pesticides are found to be 0.012, 0.095 and 0.004mg/kg respectively from first, second and third elute. The heavy metals content have been negligible.
Keywords: Argyreia speciosa; Quality control; WHO guidelines